Cytokine profile in serum and gingival crevicular fluid of children with inflammatory bowel disease: A case‐control study. Issue 7 (22nd December 2021) - Acar, Buket; Gümüş, Ersin; Özcan‐Bulut, Selcen; Özşin‐Özler, Cansu; Boyraz, Meryem Seda; Tan, Çağman; Yaz, Ismail; Özbek, Begüm; Cagdas, Deniz; Saltık‐Temizel, İnci Nur; Demir, Hülya; Özen, Hasan; et al.
Abstract: Background: To evaluate the cytokine profile in gingival crevicular fluid (GCF) and serum of pediatric inflammatory bowel disease (IBD) patients and determine the cluster patterns of cytokines. Methods: Fifty IBD patients and 21 systemically healthy children were enrolled in the study. The GCF samples were collected from the participants during periodontal examination and periodontal indices were recorded. Based on activity indexes and response to conventional treatment, patients with IBD were further categorized into subgroups as: remission, active disease, and treatment‐resistant. Serum samples were obtained from IBD patients to determine serum levels of cytokines. The levels of pro‐ (interleukin (IL)‐1β, IL‐12, IL‐21, IL‐22, IL‐23, IL‐17A, IL‐17F) and anti‐inflammatory (IL‐4, IL‐10) cytokines in serum and GCF were measured using Enzyme‐linked Immunosorbent Assay (ELISA) kits. Results: Among 50 IBD patients, 58% were in remission, 20% had active disease, and 22% were defined as treatment‐resistant. The severity of gingival inflammation measured by the criteria of Löe had increasing trends in IBD patients with active disease and treatment resistance. GCF IL‐1β level was lower and GCF IL‐4 and GCF IL‐23 levels were higher in IBD patients compared to healthy controls. In the active disease group, more cytokine clusters occurred compared to the control group and other IBD subgroups, as explained by increased cytokine‐cytokine interactions. Conclusions: Considering the increased complexity of cytokine interactions and the increased severity of gingival inflammation in patients with active disease, it can be concluded that disease activity might have an impact on gingival inflammation in pediatric patients with IBD.